(untitled) (UUM Journal of Legal Studies, 2021)
Custody decisions are tailored to the circumstances of each case based on related principles with protection of child welfare as courts’ paramount consideration. This paper seeks to understand custody issue from quantitative viewpoint through a conceptual model and examines how child custody principles have influenced loss decisions for mothers. The methodology used was content analysis and Chi-Square correlation, with usable data provided by 47 cases decided in Malaysia between 1987 and 2017 based on Act 303. Coding instrument and conceptual framework were developed with items covering presumption of maternal custody, custodian qualification and loss of rights, child’s and mother’s wishes. The findings revealed that mothers were less likely to lose custody cases and when they did their defeats were strongly influenced by factors relating to children’s preference and status quo arrangement. The results contribute to an understanding of how mothers can lose custody of their children and clarify whether some of the independent variables are used more regularly and are more predictive of the loss decisions than the others.